A Systematic Review of Methods Used to Assess Mid-Palatal Suture Maturation - Mahdian, Arezoo; Shaykhian, Shekoofeh; Behnaz, Mohammad (Journal of Dental School, 2019)
Objectives Use of a reliable method to determine the degree of skeletal development of the mid-palatal suture is important in the choice of treatment between orthopedic maxillary expansion and surgical expansion in adolescents and young adults. The aim of this study was to review the new methods for evaluation of mid-palatal suture maturation. Methods Electronic search was conducted in PubMed and Scopus databases using the following key words: (“mid-palatal suture maturation” OR “mid-palatal suture ossification”) AND (“orthopedic treatment” OR “maxillary expansion” OR “orthodontic*”) to find studies published from 1990 to December 2018 in English that evaluated the mid-palatal suture maturation stage. Results Of 127 papers found, 28 articles met the inclusion criteria and their full texts were reviewed. Finally, 8 met the inclusion criteria. Five studies used cone-beam computed tomography (CBCT) as the imaging modality and examined the quality of the mid-palatal suture maturation and assessed the morphology of the suture. Two studies used bone density and one study used fractal dimensions. Conclusion Since all the innovative methods lack a gold standard and valid histological references, it is not possible to reach a comprehensive conclusion. It is therefore important that the clinicians use several diagnostic criteria for thorough evaluation of the development of mid-palatal suture and decide on the appropriate therapeutic modality